SONOGRAPHIC EVALUATION OF THE COMMON BILE DUCT SIZE IN NORMAL ADULTS AT UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL, NIGERIA - Farate A; Umar UH; Ahmadu MS; Mustapha Z; Ahidjo A; Tahir A (Ntec Specialist, 2019)
Background: Despite ultrasound safety, affordability and its widespread use in evaluation of the diseases of biliary tree, paucity of literature on the sonographic measurements of the size of the normal adult common bile duct (CBD) in this environment exists. Objectives: To determine the normal adult diameter of the CBD in this environment using ultrasonography. Methods: This was a cross-sectional prospective study carried out at the University of Maiduguri Teaching Hospital between January to June, 2011. Results: There were 224(56%) females and 176(44%) males aged between 18 and 87 years (Mean±SD, 36.88±16.97 years). The mean AP and transverse CBD diameters (±SD) were 3.68±0.82mm and 3.89±0.86mm, respectively. The average mean for the two measurements (± SD) was 3.78±0.84mm (range = 2.0 - 6.0 mm). The mean transverse diameter was slightly greater than AP diameter (p = 0.0004).The CBD diameter was strongly correlated with age (r = 0.798; p = 0.000; r2 = 0.629). The least squares regression slope of 0.039mm±0.001 (mean±SD) was obtained suggesting 0.039mm±0.001 increase in the CBD diameter per year. There was significant correlation between the CBD diameter with weight (r = 0.504; p = 0.000) and BMI (r = 0.454; p = 0.000). No significant difference between the mean CBD diameter in males and females (p= 0.084) was observed. Conclusion: The mean and range of CBD size in normal adult population were determined and significantly correlated with age, weight, and BMI.